Impact of nurse staffing on patient and nurse workforce outcomes in acute care settings in low- and middle-income countries: a systematic review. Issue 4 (1st April 2021) - Assaye, Ashagre Molla; Wiechula, Richard; Schultz, Timothy J.; Feo, Rebecca
ABSTRACT: Objective: The objective of this review was to determine the effect of nurse staffing on patient and nurse workforce outcomes in acute care settings within low- and middle-income countries. Introduction: Health care systems in low- and middle-income countries experience a high proportion of the global burden of disease, which is aggravated by several health care constraints. The high rates of both communicable and non-communicable diseases, low numbers in the workforce, poor distribution of qualified professionals, and constraints in medical supplies and resources make the provision of quality health care challenging in low- and middle-income countries. Health care systems in low- and middle-income countries, however, are still expected to address universal health care access and provide high-quality health care. Systematic reviews examining nurse staffing and its effect on patient and nurse workforce outcomes are largely from the perspective of high-income countries. There is a need to understand the evidence on nurse staffing and its impact in the context of low- and middle-income countries. Inclusion criteria: Empirical studies that addressed acute care nurse staffing levels, such as nurse-to-patient ratio or nurses' qualifications, experience, and skill mix, and their influence on patient and nurse workforce outcomes were included in the review. Studies conducted in a low- or middle-income country were included. Outcomes must have been measured objectively using validated tools. Methods: Studies published until July 2019 were identified from CINAHL, PubMed, Scopus, Embase, PsycINFO, Cochrane Library, Web of Science, and ProQuest Dissertations and Theses. The JBI approach to critical appraisal, study selection, data extraction, and data synthesis was used for this review. Narrative synthesis was conducted due to high heterogeneity of included studies. The level of evidence was determined using GRADEpro. Results: Twenty-seven studies were included in this review and the level of evidence was low, mainly due to the design of included studies. Low nurse-to-patient ratio or high nurse workload was associated with higher rates of in-hospital mortality, hospital-acquired infection, medication errors, falls, and abandonment of treatment. Findings on the effect of nurse staffing on length of hospital stay and incidence of pressure ulcers were inconsistent. Extended work hours, less experience, and working night or weekend shifts all significantly increased medication errors. Higher nurse workload was linked to higher levels of nurses' burnout, needlestick and sharps injuries, intent to leave, and absenteeism. Conclusions: Lower nurse-to-patient ratios and higher nurse workload are linked to in-hospital mortality, hospital-acquired infections, and medication errors among patients, and high levels of burnout, needlestick and sharps injuries, absenteeism, and intention to leave their job among nurses in low- and middle-income countries. The results of this review show similarities with the evidence from high-income countries regarding poor outcomes for patients and nurses. These findings should be considered in light of the lower nurse-to-patient ratios in most low- and middle-income countries. Systematic review registration number: PROSPERO CRD42018119428